A continuous-time multi-echelon inventory model with transshipment. Issue 4 (2015) - Tai, Allen H.
In this paper, we propose a continuous-time model for a multi-echelon inventory system. Items stored in the inventory are deteriorating and deteriorated items are screened out continuously from the inventory. Lateral transshipments are allowed among the warehouses in the same echelon. The transshipment rate depends on the inventory level of the corresponding warehouses. In this study, we give some sufficient conditions for the equilibrium points of the system to be stable. By aggregating the warehouses in an echelon, a procedure is developed for finding the equilibrium value of inventory level at each warehouse. The results can be applied in determining the transshipment rate among the warehouses.